2005
DOI: 10.1021/ma050827j
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Flow-Induced Anisotropic Thermal Conduction in a Polyisobutylene Melt Following Step Shear Flow

Abstract: Flow-induced anisotropic thermal conduction in a polyisobutylene melt subjected to shear deformations is studied experimentally. Time-dependent measurements of the full (four components) thermal diffusivity tensor following step shear strain flow are presented. These data were obtained with a novel experimental setup based on the optical technique of forced Rayleigh scattering. Birefringence and stress measurements are made for the same flow, and the well-known stress-thermal rule is found to be satisfied. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 27 publications
6
16
1
Order By: Relevance
“…This has been attributed to the well packing of polymer chains in such a narrow pore which facilitates the heat conduction through collisions. 22 As a comparison of the effect of chain anisotropy on the thermal conductivity anisotropy, observed in this work, with previous literature we may address to the experimental reports by Balasubramanian et al 41,42 on the increase in the thermal conductivity of bulk liquid polyisobutylene under shear and to the theoretical findings on the anisotropies in the thermal conductivities of stretched bulk polymer melts and bulk crystalline polymers. [26][27][28][29][30] …”
Section: Anisotropy In Thermal Conductivitiessupporting
confidence: 53%
“…This has been attributed to the well packing of polymer chains in such a narrow pore which facilitates the heat conduction through collisions. 22 As a comparison of the effect of chain anisotropy on the thermal conductivity anisotropy, observed in this work, with previous literature we may address to the experimental reports by Balasubramanian et al 41,42 on the increase in the thermal conductivity of bulk liquid polyisobutylene under shear and to the theoretical findings on the anisotropies in the thermal conductivities of stretched bulk polymer melts and bulk crystalline polymers. [26][27][28][29][30] …”
Section: Anisotropy In Thermal Conductivitiessupporting
confidence: 53%
“…(l) is valid for both cross-linked PBD elastomers in simple elongation. Values of the stress-thermal coefficient obtained from the data in Figure 3 normalized by GN is roughly GNQ ~ 0.06+0.01, which is consistent with values obtained from previously studied systems [4][5][6]. …”
Section: Resultssupporting
confidence: 89%
“…In previous work, we have shown that Eq. (I), sometimes referred to as the 'stress-thermal rule,' is valid for polymer liquids in shear deformations, and for a cross-linked siUcone rubber in simple elongation [4][5][6]. In this study, we examine the validity of the stress-thermal rule on cross-linked polybutadiene elastomers in uniaxial elongation.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that pcp is independent of deformation [20], the anisotropy in thermal diffusivity is equiva lent to that of thermal conductivity. Using this technique, we have obtained components of the full thermal diffusivity (conductivity) tensor in polymers subjected to uni-axial elongation [21][22][23][24][25] and shear flow [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…(2) is the product of keq, the equilibrium thermal conductivity, and Ct, the stress-thermal coefficient, which is analogous to the stress-optic coefficient. In the previous work [21][22][23][24][25][26][27][28], we have combined measurements of the thermal conductivity tensor (using FRS) and stress tensor in deformed polymeric systems to provide the first (and only) tests of the stress-thermal rule. For all systems considered thus far, the stress-thermal rule has been found to be valid.…”
Section: Introductionmentioning
confidence: 99%